Rapid and Reliable Formation of Highly Densified Bilayer Oxide Dielectrics on Silicon Substrates via DUV Photoactivation for Low-Voltage Solution-Processed Oxide Thin-Film Transistors - Lee, Won June; Choi, Jun Gyu; Sung, Sujin; Kim, Chang Hyun; Na, Sekwon; Joo, Young Chang; Park, Sungjun; Yoon, Myung Han (ACS Applied Materials and Interfaces, 2021)
In this research, we report the rapid and reliable formation of high-performance nanoscale bilayer oxide dielectrics on silicon substrates via low-temperature deep ultraviolet (DUV) photoactivation. The optical analysis of sol-gel aluminum oxide films prepared at various concentrations reveals the processable film thickness with DUV photoactivation and its possible generalization to the formation of various metal oxide films on silicon substrates. The physicochemical and electrical characterizations confirm that DUV photoactivation accelerates the efficient formation of a highly dense aluminum oxide and aluminum silicate bilayer (17 nm) on heavily doped silicon at 150 °C within 5 min owing to the efficient thermal conduction on silicon, resulting in excellent dielectric properties in terms of low leakage current (∼10-8 A/cm2 at 1.0 MV/cm) and high areal capacitance (∼0.4 μF/cm2 at 100 kHz) with narrow statistical distributions. Additionally, the sol-gel bilayer oxide dielectrics are successfully combined with a sol-gel indium-gallium-zinc oxide semiconductor via two successive DUV photoactivation cycles, leading to the efficient fabrication of solution-processed oxide thin-film transistors on silicon substrates with an operational voltage below 0.5 V. We expect that in combination with large-area printing, the bilayer oxide dielectrics are beneficial for large-area solution-based oxide electronics on silicon substrates, while DUV photoactivation can be applied to various types of solution-processed functional metal oxides such as phase-transition memories, ferroelectrics, photocatalysts, charge-transporting interlayers and passivation layers, etc. on silicon substrates.
Keywords: Electrical characterization; Heavily doped silicons; Indium gallium zinc oxides; Low voltage solutions; Operational voltage; Oxide thin-film transistors; Reliable formations; Statistical distribution; bilayer oxide dielectrics; deep ultraviolet; photoactivation; sol-gel metal oxides; thin-film transistors